Chemokine receptor CXCR7 is a functional receptor for CXCL12 in brain endothelial cells. - Yang Liu; Eleanor Carson-Walter; Kevin A Walter (PLoS ONE, 2014)
The chemokine CXCL12 regulates multiple cell functions through its receptor, CXCR4. However, recent studies have shown that CXCL12 also binds a second receptor, CXCR7, to potentiate signal transduction and cell activity. In contrast to CXCL12/CXCR4, few studies have focused on the role of CXCR7 in vascular biology and its role in human brain microvascular endothelial cells (HBMECs) remains unclear. In this report, we used complementary methods, including immunocytofluorescence, Western blot, and flow cytometry analyses, to demonstrate that CXCR7 was expressed on HBMECs. We then employed short hairpin RNA (shRNA) technology to knockdown CXCR7 in HBMECs. Knockdown of CXCR7 in HBMECs resulted in significantly reduced HBMEC proliferation, tube formation, and migration, as well as adhesion to matrigel and tumor cells. Blocking CXCR7 with a specific antibody or small molecule antagonist similarly disrupted HBMEC binding to matrigel or tumor cells. We found that tumor necrosis factor (TNF)-α induced CXCR7 in a time and dose-response manner and that this increase preceded an increase in vascular cell adhesion molecule-1 (VCAM-1). Knockdown of CXCR7 resulted in suppression of VCAM-1, suggesting that the reduced binding of CXCR7-knockdown HBMECs may result from suppression of VCAM-1. Collectively, CXCR7 acted as a functional receptor for CXCL12 in brain endothelial cells. Targeting CXCR7 in tumor vasculature may provide novel opportunities for improving brain tumor therapy.